Transportation and Canal Centering Ability of Reciprocating vs Full Rotating Files after Instrumenting Severely Curved Canals. A Cone Beam Computed Tomography Comparative Study - Maya Eter; Roula S Abiad (Publymed, 2024)
Background: Canal curvature is a major risk factor for canal transportation, which in turn causes that many parts of the root canal system remain untouched leading to persistence of microorganisms and debris, promoting structural weakening, and compromising the apical seal. Aim: To compare canal transportation and centering ability of reciprocating systems vs full rotating systems after instrumenting severely curved canals, using CBCT. Methodology: Ninety curved roots from extracted human molars were scanned using CBCT, assigned to six groups according to the file system used for instrumentation, namely: WaveOne Gold, RECIPROC blue, R-motion, RACE-EVO, 2Shape and Hyflex EDM, then rescanned after chemo-mechanical. Centering ability and transportation were evaluated at three levels using Gambil's method. Results: All tested files caused minimal transportation at all levels. No significant differences were found between groups regarding transportation at the apical and coronal levels. Only at the middle level, R-motion showed significantly less transportation than WaveOne Gold and 2Shape. No significant differences were found between all the tested files regarding centering ability at all levels. Conclusion: File motion whether reciprocating or full rotating has no effect on canal transportation and canal centering ability while shaping severely curved canals.